1977
DOI: 10.1111/j.1360-0443.1977.tb03968.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of a Therapeutic Community for Former Drug Users

Abstract: A descriptive account is given ofthe operation of one ofthefirst Concept-Based Therapeutic Communities to be estabtished in the U.K. The concept of a totat institution was found useful to understanding the practice of the program. The first 100 residents admitted to the house were followed up mainly by personal interview once the majority had left the house for al least six months. Overatl, the achievements ofthe house were simitar to those of Concept houses in the U.S. Onty a minority ofatt admissions complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The present results are in line with other evidence from Concept Houses (Ogborne and Melotte, 1977;Smart, 1976) in suggesting that a treatment effect occurs which is closely related to the length of time an individual resides in the community. The present evidence indicates that those people staying for more than six months (approximately one third of all admissions) have the most successful outcome.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The present results are in line with other evidence from Concept Houses (Ogborne and Melotte, 1977;Smart, 1976) in suggesting that a treatment effect occurs which is closely related to the length of time an individual resides in the community. The present evidence indicates that those people staying for more than six months (approximately one third of all admissions) have the most successful outcome.…”
Section: Resultssupporting
confidence: 92%
“…The programme is ofthe 'Concept House' type and has been briefly described in another publication (Jeffrey et al, 1977). More detailed descriptions of such programmes are provided by Sugarman (1974) and Ogborne and Melotte (1977).…”
mentioning
confidence: 99%
“…As a result of the practical need to evaluate whether or not the TC 'works' a number of pragmatic research approaches have developed. For example, although it has been suggested that treatment success 5 should be defined and represented through the individual change that people make during and after programme participation (DeLeon, 2000) attempts to represent success though crude outcome measures such as relapse, reconviction and retention dominate existing empirical evidence (Ogbourne and Melotte, 1977;DeLeon, Wexler and Jainchill, 1982;Condelli and Hubbard, 1994; Page and Mitchell, 1998;Smith et al, 2006; Malivert et al, 2012;Vanderplasschen et al, 2013). The utilisation of absolute, standardised measures to demonstrate the success of a complex life-long process that begins within a person-centred environment has not only produced research with an array of conceptual and methodological issues but maintained the air of ambiguity which surrounds the day-to-day workings of a TC (Gosling, 2015).…”
Section: The Therapeutic Communitymentioning
confidence: 99%
“…In fact, however, several follow‐up studies from different TCs were published in Scandinavia and in England in the 1970s. Ogborne and Malotte (1977) conducted a study of the first 100 residents admitted to a TC founded on the concept‐based philosophy in London in 1970. In the follow‐up study, 87 of the former residents were personally interviewed at least six months after they had left the programme.…”
Section: European Tc Researchmentioning
confidence: 99%